Synergistic interaction of two antimalarial drugs, artemisinin and concanamycin A - Zahari, Nurul Izzaty Najwa; Ujal, Noor Fardziatun; Abu-Bakar, Nurhidanatasha (Life Sciences, Medicine and Biomedicine, 2023)
Artemisinin is a powerful drug that has been combined with other antimalarial drugs to combat malaria and it has been crucial to recent achievements in reducing malaria cases. However, the emergence of Plasmodium falciparum resistance against artemisinin has become a serious problem in malaria treatment. Our previous studies reported that artemisinin alkalinised the digestive vacuole of P. falciparum similarly to concanamycin A. Concanamycin A is a specific inhibitor of V-type H+-ATPase, a proton pump located on the membrane of the digestive vacuole. A study also showed that a low concentration of concanamycin A is required to kill 50% of the parasites. Therefore, this study aimed to determine the interaction of artemisinin with concanamycin A by using the isobologram analysis of effects on parasite growth. The antimalarial activity (IC50) of artemisinin and concanamycin A was evaluated by using a malarial SBYR Green I fluorescence-based (MSF) assay prior to isobologram analysis. Based on their IC50 values, six different combination solutions of the drugs were assigned and used in the isobologram analysis. The IC50 of artemisinin and concanamycin A was 13 ± 2.52 nM and 7 ± 1.15 nM, respectively. The interaction of artemisinin and concanamycin A was found to be synergistic, indicating that the combination of these drugs could kill the parasites more effectively. This study suggests that artemisinin and concanamycin A combination can be a new candidate in artemisinin-based combination therapies.